2014
DOI: 10.5539/gjhs.v6n4p205
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Immunosuppressive Medications Adherence and Quality of Life and Some Patient Factors in Renal Transplant Patients in Iran

Abstract: Background & Aim:About organ transplant, immunosuppressive medications adherence is a critical issue, because non-adherence to these medications causes rejection, reduces quality of life and increases treatment cost and mortality rate. Among these, the quality of life is deemed very important to evaluate treatment result and also it can be useful for discovering non adherence. The aim this study was to assess the relationship between medication adherence and quality of life and some patient factors in renal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Some studies have already shown that high religiosity is associated with adherence in some contexts, such as chronic diseases . In KT patients, a study in Iran found that a higher psychological‐spiritual dimension of quality of life was correlated with adherence, which is in accordance with our findings . In fact, religion plays an important role for the patient with chronic kidney disease at an advanced stage, most of the time ameliorating the doctor‐patient relationship, quality of life and coping with the disease .…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have already shown that high religiosity is associated with adherence in some contexts, such as chronic diseases . In KT patients, a study in Iran found that a higher psychological‐spiritual dimension of quality of life was correlated with adherence, which is in accordance with our findings . In fact, religion plays an important role for the patient with chronic kidney disease at an advanced stage, most of the time ameliorating the doctor‐patient relationship, quality of life and coping with the disease .…”
Section: Discussionsupporting
confidence: 91%
“…Successful long‐term kidney graft outcomes remain suboptimal, with immunosuppressant medication non‐adherence considered an important contributing factor . Currently, immunosuppressant medication non‐adherence in renal transplant patients is reported to be between 20% and 60% …”
mentioning
confidence: 99%
“…5 Currently, immunosuppressant medication non-adherence in renal transplant patients is reported to be between 20% and 60%. [6][7][8][9] Several barriers to immunosuppressant adherence have been consistently reported including: a complex dosing regimen, 10,11 patient age (<35 years), 12,13 forgetfulness, 14,15 beliefs (about medicines, the transplant, and who/what controls an individual's health), 6,16 depression or anxiety, 17 high medication cost, 1,11 perceived/actual side-effects, 4,15,18 and lack of social support. 4 Identifying barriers impacting adherence is crucial to understanding how best to deliver interventions to address these barriers.…”
mentioning
confidence: 99%
“…The data available to date suggest that pre and post-transplant screening process must include both a medical evaluation and a thorough psychological and psychiatric assessment for a better therapeutic adherence. Adherence is a very important issue in the medical care of kidney transplant patients (51). The life style and quality of life of a transplanted subject represent a key point, and it is essential to adhere to the therapy and prescribed behaviors (34,79).…”
Section: Discussionmentioning
confidence: 99%